Reasons for admission and rehabilitation rates of various wildlife species in Finland - White, Kati; Hänninen, Laura; Sainmaa, Sanna; Valros, Anna (Frontiers in Veterinary Science, 2024)
Wildlife rehabilitation is a common part of animal-protection work. In Finland wildlife care is usually based on volunteer work and no licensing or training is required. Wildlife casualties are also treated professionally in some contexts such as zoos. The species of wildlife casualties may influence treatment decisions. Our anonymous online survey examined wildlife caregiving practices in Finland (n = 78), focusing on the care provided to various animal species and the outcomes of rehabilitation efforts. The survey was sent to both veterinarians and volunteers caring for wildlife, and it was part of a larger survey. Questions were mainly closed, and opinion-related questions were applied on a Likert scale (1–7; where 1 meant strongly disagree and 7 meant strongly agree). Most respondents primarily cared for mammals and birds. Reptiles, amphibians, and fish received less attention. Injuries and overwinter survival, especially in the case of hedgehogs, were the primary reasons for wildlife admissions. The training background of the rehabilitators varied and was related to the animal species being treated. Those caring mainly for hedgehogs (Erinaceus europaeus) were the least likely to have animal-related training or long-term experience in wildlife care. We show a notably high rehabilitation rate of approximately 80% of commonly treated species, significantly surpassing figures from other countries, which raises concerns that animals are admitted or released on too light grounds, leading to animal welfare problems. It is also noteworthy that only one-fifth of respondents said they kept records of animal admissions. Less than 40% of respondents emphasized the need for further education on any specific issue, which may indicate overestimation of personal skills. In conclusion, our study raises concerns regarding the ethics and potential harm associated with wildlife rehabilitation.